"Recens-arche" filozofii Józefa Bańki - Nierodka, Paweł (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2010)
In my paper I raised the issue of time and focused on its recentivistic aspect. While discerning physical time from anthropological time I emphasized the meanings of "thymical" time. Such an aspect of time indicates not so much the relation of present time with the human as the direction of the lapse of time. Everything starts from and ends with our "now", our present as the only existing one. The recentivistic concept of time is a return to the source of philosophy, source of philosophic considerations about the existence in view of contemporary "blurring" of philosophic deliberations. "Escape from the present" drives the humans into the cave of life through the past of the wasted chances or the future of the envisaged successes. The principal thesis of the deliberations conducted says there is no existence, thoughts, world, and, finally, the very human being without recens. Without recens there is even no present which continues the time.